A Modified Two-Way Active Avoidance Test for Combined Contextual and Auditory Instrumental Conditioning - Salah, Houssein; Abdel Rassoul, Ronza; Medlej, Yasser; Asdikian, Rita; Hajjar, Helene; Dagher, Sarah; Darwich, Mouhamad; Fakih, Christina; Obeid, Makram (Frontiers in Behavioral Neuroscience, 2021)
Available two-way active avoidance paradigms do not provide contextual testing, likely due to challenges in performing repetitive trials of context exposure. To incorporate contextual conditioning in the two-way shuttle box, we contextually modified one of the chambers of a standard two-chamber rat shuttle box with visual cues consisting of objects and black and white stripes patterns. During the 5 training days, electrical foot-shocks were delivered every 10 s in the contextually modified chamber but were signaled by a tone in the plain chamber. Shuttling between chambers prevented an incoming foot-shock (avoidance) or aborted an ongoing one (escape). During contextual retention testing, rats were allowed to freely roam in the box. During auditory retention testing, visual cues were removed, and tone-signaled shocks were delivered in both chambers. Avoidance gradually replaced escape or freezing behaviors reaching 80% on the last training day in both chambers. Rats spent twice more time in the plain chamber during contextual retention testing and had 90% avoidance rates during auditory retention testing. Our modified test successfully assesses both auditory and contextual two-way active avoidance. By efficiently expanding its array of outcomes, our novel test will complement standard two-way active avoidance in mechanistic studies and will improve its applications in translational research.